REPRESENTASI HUBUNGAN KELUARGA DALAM FILM “NANTI KITA CERITA TENTANG HARI INI" - Nabilah Khairunnisa; Anisti; Tuty Mutiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Family relationships are a fundamental aspect of every society, consistently reflecting values such as love, support, and understanding. This research aims to explore and analyze how family relationships are portrayed in the film "Nanti Kita Cerita Tentang Hari Ini," directed by Angga Dwimas Sasongko. Utilizing a descriptive qualitative approach and Roland Barthes' semiotic theory, this study examines key scenes, dialogues, and visual symbols that contribute to both the explicit and implicit meanings of family interactions. The analysis reveals that the film successfully illustrates various facets of family relationships, from harmony to conflict. This representation encompasses complex communication, parental expectations, individual struggles, and the processes of acceptance and conflict resolution. The film serves as a powerful medium that mirrors and shapes public understanding of the realities of family life in Indonesia. It also highlights cinema's role in fostering discussions about the importance of empathy and acceptance within the family unit.